2018 IEEE Wireless Communications and Networking Conference Workshops (WCNCW) 2018
DOI: 10.1109/wcncw.2018.8369025
|View full text |Cite
|
Sign up to set email alerts
|

Robust massive MIMO equilization for mmWave systems with low resolution ADCs

Abstract: Leveraging the available millimeter wave spectrum will be important for 5G. In this work, we investigate the performance of digital beamforming with low resolution ADCs based on link level simulations including channel estimation, MIMO equalization and channel decoding. We consider the recently agreed 3GPP NR type 1 OFDM reference signals. The comparison shows sequential DCD outperforms MMSE-based MIMO equalization both in terms of detection performance and complexity. We also show that the DCD based algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Besides, if the imperfections of the AGC is in the range of −20% to 20%, there is no major influence on the performance. In [210], the performance of digital beamforming with low-resolution ADCs based on link level simulations was investigated. In their observations, they found that the complexity of MMSE equalization is dominated by the computation of the gram matrix and not the matrix inversion.…”
Section: Millimeter-wave Massive Mimo Systems With Low-resolution Adcsmentioning
confidence: 99%
“…Besides, if the imperfections of the AGC is in the range of −20% to 20%, there is no major influence on the performance. In [210], the performance of digital beamforming with low-resolution ADCs based on link level simulations was investigated. In their observations, they found that the complexity of MMSE equalization is dominated by the computation of the gram matrix and not the matrix inversion.…”
Section: Millimeter-wave Massive Mimo Systems With Low-resolution Adcsmentioning
confidence: 99%
“…As in [8] we use an unbiased MMSE receiver for the MIMO equalization. We use the channel estimates to generate the MMSE MIMO equalizer.…”
Section: B Link-level Simulation Based Rate Evaluationmentioning
confidence: 99%
“…Due to the limited space not all details are given. In this work we only describe the overview and the differences with our theoretical evaluation in [1] and the link-level evaluation in [8]. The remaining paper is organized as follows: In the first section we present the chosen channel estimation method as well as the model for the theoretical evaluation.…”
Section: Introductionmentioning
confidence: 99%